Law Enforcement Againts Corruption Crimes (A Case Study of Village Land Misuse in Sleman Regency) - Zidni, Irfan; Tahir, Ach (UIN Sunan Kalijaga Yogyakarta, 2024)
Corruption is a significant crime requiring extraordinary measures for its eradication. The legal framework for addressing corruption in Indonesia is provided by Law No. 31 of 1999, amended by Law No. 20 of 2001 concerning the Eradication of Corruption Crimes. Despite this, corruption is frequently perpetrated by government officials who are expected to avoid corruption, collusion, and nepotism. An example of this can be observed in Sleman Regency, where government officials have been implicated in the misuse of village land. This land, intended as a source of village income, is often exploited, becoming a focal point for corruption. This research focuses on the law enforcement mechanisms and the challenges encountered by the Yogyakarta High Prosecutor's Office in addressing corruption cases related to village land in Sleman Regency. This study employs a field research design with a juridical-empirical approach. Data collection was conducted through structured interviews. The analysis method is qualitative, involving a detailed descriptive analysis of the data collected from the field, which is then correlated with existing legal regulations. Furthermore, the research utilizes two theoretical frameworks for analysis: the law enforcement theory and the fraud triangle. The result of this study is a law enforcement effort carried out by Kejati DIY on the criminal offences of corruption cases of land abuse in the village district of Sleman was done through preventive and repressive efforts. The repressive attempt was to conduct investigations, investigations and prosecutions in accordance with both the Constitution and the Criminal Code of Corruption. Although the implementation of the DIY is still impressed by the